Mode of Islamic bank financing: Does effectiveness of shari’ah supervisory board matter? - Waemustafa, Waeibrorheem; Abdullah, Azrul (INSInet Publications, 2015)
This paper examines the relationships between the effectiveness of Shariah supervisory board (SSB), their remuneration and mode of financing Islamic bank. The SSB effectiveness is evaluated by an index based on 9 attributes score. This study comprises 18 Islamic banks in which operating in Malaysia from the year 2012 to 2013 as a sample. Our regression analysis shows that the effectiveness of SSB does not concern with the mode of Islamic bank financing. However, we found that SSB remuneration and bank’s financial growth shown a positive and significant relationship with mode of financing. The implications of these findings are discussed.